Bioautographic screening for natural quinolone antimicrobial agents from Glycosmis pentaphylla (Retz.) DC., Ruta angustifolia (L.) Pers. and Lunasia amara Blanco - Md Taib, Nurhaya; Mohd Kamal, Laina Zarisa; Mohd Hassan, Norazian; Khin Soe, May; Abdul Karim, Khairul Anuar (2009)
Background